Distress risk anomaly and misvaluation - Andreou, Christoforos K.; Lambertides, Neophytos; Panayides, Photis (My University, 2021)
This paper examines the effects of misvaluation on the well-documented negative relation between distress risk and stock returns (distress risk anomaly). Findings indicate that distress risk is negatively related to subsequent stock returns only in the subset of the most overvalued stocks, which is consistent with mispricing explanations provided by prior studies. The distress anomaly disappears after controlling for mispricing effects. Further analysis reveals earnings management to be one possible cause for the overvaluation of highly distressed firms. The results are robust to alternative specifications of distress risk and mispricing measures.
Keywords: Distress risk; Mispricing; Earnings management; Asset pricing anomalies